Edukasi Pentingnya Membaca dan Menulis di SD 01 Sindangbarang - Lutfi Eskawati; Sigit Andi Prasetya Dinata; Sebriana Cahya Eri (Universitas Muhammadiyah Manado, 2022)
In the 21st century, reading and writing are the main assets that must be mastered by each individual. Individuals who have the ability and expertise in reading and writing tend to have critical, creative and innovative thinking. Every individual has different reading and writing abilities. A person's ability to read and write is influenced by the environment in which he grows up. Each country has a different level of interest in reading. Reading and writing are parts of life that cannot be separated. Reading and writing are like keys to open the door to civilization in a society. In our nation's culture, reading and writing have become a part of every part of Indonesian society's life. However, in reality, currently Indonesia is faced with low public interest in reading. Here I will explain why reading and writing are very important in encouraging the progress of a nation.